PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA GURU PADA SMP NEGERI 22 KOTA BEKASI - Abdul Rahmanto; Edward Efendi Silalahi (Bajang Institute, 2023)
thesis entitled Effect of Work Environment and Job Satisfaction on Teacher Work Discipline at SMP Negeri 22 Bekasi City. This study aims to determine whether the variables of work environment and job satisfaction simultaneously or partially have a significant effect on work discipline. The population in this study were 55 people who were assigned as teaching staff, SMP Negeri 22 Bekasi City having the address at Jl. Bintara, Bintara Jaya, Bekasi City. Collecting data in this study using questionnaires and data processing and hypothesis testing using the IBM SPSS Statistics Version 25 application program. This has been proven by the multiple linear regression equation obtained is Y = 2.263+0.282(X₁)+0.405(X₂). Simultaneously the results obtained from this study are that the variables of work environment and job satisfaction have a significant influence on the teacher's work discipline variable, with results showing f count > f table of f count 36,921 > f table 3,175. Partially the results show that the work environment variable has a significant effect on work discipline, with the results showing the value of t arithmetic 3,371 > t table 2.006 and sig. 0,02 < 0.05 and the variable job satisfaction also has a significant effect on Work Discipline with the results showing the t count of 3,346 > 1,674 and the value of sig. 0,002 < 0,05